Daya tarik saham bank bca bagi investor jangka panjang: analisis keuangan dan prospek masa depan - Irawati, Indriana (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the stock investment prospects of PT Bank Central Asia Tbk. (BCA) by reviewing its financial performance, operational stability, and competitiveness in the capital market over the past five years (2020-2024). Through a descriptive statistical approach, data on stock price trends, financial statements, and Return on Equity (ROE) ratios are evaluated to provide an overview of future investment potential. The results of the analysis show that BCA shares experienced significant growth, despite being affected by the COVID-19 pandemic in 2019-2020. The steady increase in net profit, total assets, and total equity reflects the company's expansion and efficiency. Consistent ROE values above 15% demonstrate management's ability to effectively utilize capital to generate profits. With positive growth trends and adaptability to economic challenges, BCA shares are a promising investment option for the long term